2023
DOI: 10.3389/fcell.2023.1174535
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer and single-cell analysis reveal the prognostic value and immune response of NQO1

Liping Shen,
Shan Jiang,
Yu Yang
et al.

Abstract: Background: Overexpression of the NAD(P)H: Quinone Oxidoreductase 1 (NQOI) gene has been linked with tumor progression, aggressiveness, drug resistance, and poor patient prognosis. Most research has described the biological function of the NQO1 in certain types and limited samples, but a comprehensive understanding of the NQO1’s function and clinical importance at the pan-cancer level is scarce. More research is needed to understand the role of NQO1 in tumor infiltration, and immune checkpoint inhibitors in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…Liping Shen et al conducted a pan cancer research of NQO1 and found that NQO1 was significantly upregulated in most cancer types. The scRNA-seq analysis revealed a potential relationship between the NQO1 mRNA expression levels and the infiltration of immune cells and stromal cells, and inhibition of NQO1 might be a promising strategy for cancer immunotherapy (43). Likewise, Xinmiao Xue et al identified NT5E as a novel prognostic biomarker in a pan-cancer analysis.…”
Section: Tme and Insight Into Immunotherapymentioning
confidence: 99%
“…Liping Shen et al conducted a pan cancer research of NQO1 and found that NQO1 was significantly upregulated in most cancer types. The scRNA-seq analysis revealed a potential relationship between the NQO1 mRNA expression levels and the infiltration of immune cells and stromal cells, and inhibition of NQO1 might be a promising strategy for cancer immunotherapy (43). Likewise, Xinmiao Xue et al identified NT5E as a novel prognostic biomarker in a pan-cancer analysis.…”
Section: Tme and Insight Into Immunotherapymentioning
confidence: 99%